An ultra-early-strength and abrasion-resistant concrete and a preparation method thereof

CN122878093APending Publication Date: 2026-10-09HUBEI UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611351213.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-02
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0004]然而,现有的同步注浆料主要是以普通硅酸盐水泥和火山灰质掺合料为主要胶凝材料,天然矿产资源为骨料,添加价格高的各种纤维,按照一定比例配制而成的,早期强度较低,而目前优质资源日渐缺乏

Benefits of technology

(1)本发明采用超细水泥复配体系搭配复合减水分散剂、悬浮稳定剂与消泡剂,有效优化混凝土浆体状态。制备的混凝土拌合物和易性极佳,坍落扩展度可达600mm以上,具备自流平、自密实特性;同时浆体稳定性优异,施工过程中无泌水、分层、离析问题,粘度适中、成型细腻光滑,无需复杂振捣工艺,大幅简化施工操作、提升施工效率,适配各类现场浇筑施工场景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application provides a super-early-strength and wear-resistant concrete and a preparation method thereof. The super-early-strength and wear-resistant concrete comprises the following components in parts by weight: ultra-fine cement 535-610 parts, wear-resistant powder 20-55 parts, waste and old ceramic wear-resistant fine aggregate 510-625 parts, waste and old ceramic wear-resistant coarse aggregate 755-910 parts, water-reducing dispersant 0.8-1.6 parts, suspension stabilizer 1.2-1.9 parts, defoaming agent 0.12-0.18 parts, anti-seepage and water-repellent agent 2-8 parts, and dense reinforcing component 4-12 parts. The application uses the high-cementing-efficiency ultra-fine cement and the wear-resistant coarse and fine aggregate prepared from waste and old ceramics as main raw materials, and combines the wear-resistant powder and various functional additives to replace the admixture and the additive of the traditional concrete, so that the prepared super-early-strength and wear-resistant concrete has high workability, super-high early strength, high late strength, high water resistance and high wear resistance. Meanwhile, the resource utilization of the waste and old ceramics is beneficial to the secondary utilization of solid waste resources.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building materials technology, and more specifically, to an ultra-early strength impact-resistant concrete and its preparation method. Background Technology

[0002] In special applications such as hydraulic engineering (e.g., spillway tunnels, overflow dams, stilling basins), transportation engineering (e.g., highway pavements, airport runways, bridge expansion joints), and coastal ports), concrete structures endure harsh service conditions for extended periods, including high-speed, sand-laden water flows, silt impacts, and repeated impacts from heavy vehicles. The resulting abrasion damage is a major factor contributing to structural degradation and even premature failure. Abrasion damage typically manifests as surface spalling due to bedload impact, gradual loss of slurry due to suspended mass abrasion, and cavitation damage under high head conditions. These forms of damage often overlap, accelerating the deterioration process. Therefore, developing concrete materials with excellent abrasion resistance is crucial for extending the service life of these engineering structures and reducing maintenance costs.

[0003] In improving the impact and abrasion resistance of concrete, existing technologies mainly optimize the material composition, including: incorporating auxiliary cementitious materials such as silica fume, fly ash, and slag to improve the composition of hydration products and matrix density; adding steel fibers, polypropylene fibers, or polyvinyl alcohol fibers to enhance matrix toughness and crack resistance; replacing ordinary aggregates with wear-resistant aggregates such as iron ore and quartz sand; and incorporating rubber particles to absorb impact energy. Among these, silica fume, due to its combination of pozzolanic activity and micro-aggregate filling effect, has a particularly significant effect on improving impact and abrasion resistance and has been widely used in various types of impact and abrasion-resistant concrete. Ultra-high performance concrete, with its extremely high density and excellent mechanical properties, has also been proven to have outstanding impact and abrasion resistance.

[0004] However, existing synchronous grouting materials mainly use ordinary Portland cement and pozzolanic admixtures as the main cementing materials, natural mineral resources as aggregates, and various expensive fibers added in a certain proportion. These materials have low early strength, and high-quality resources are becoming increasingly scarce. Using treated solid waste as the main raw material to produce wear-resistant concrete can solve the problem of high-quality resource shortage. Furthermore, in engineering scenarios requiring rapid traffic restoration or emergency repairs, the early strength development speed of concrete is also crucial. Ultra-early strength concrete can reach design requirements within hours to days, thus significantly shortening the construction cycle.

[0005] To address the aforementioned technical issues, it is necessary to develop a new type of concrete material that combines ultra-early strength with excellent impact and abrasion resistance, so as to simultaneously meet the engineering requirements of rapid construction and long-term durability. Summary of the Invention

[0006] In view of this, the present invention provides an ultra-early strength abrasion-resistant concrete and its preparation method, which uses waste ceramics as coarse and fine aggregates to obtain a low-cost, high-performance abrasion-resistant concrete based on solid waste.

[0007] To achieve the above objectives, the present invention provides an ultra-early strength abrasion-resistant concrete, which is composed of the following components in parts by weight: 535-610 parts of ultrafine cement, 20-55 parts of abrasion-resistant powder, 510-625 parts of waste ceramic abrasion-resistant fine aggregate, 755-910 parts of waste ceramic abrasion-resistant coarse aggregate, 0.8-1.6 parts of water-reducing dispersant, 1.2-1.9 parts of suspension stabilizer, 0.12-0.18 parts of defoamer, 2-8 parts of impermeable and water-repellent agent, and 4-12 parts of compacting reinforcement component.

[0008] Furthermore, the ultrafine cement is a composite system of ultrafine ordinary silicate cement and ultrafine sulfoaluminate cement; the wear-resistant powder is at least one of corundum powder and glass powder; the waste ceramic wear-resistant fine aggregate and waste ceramic wear-resistant coarse aggregate are both selected from waste household ceramics and waste ceramic bricks; the water-reducing and dispersing agent is a composite system of polycarboxylate high-performance water-reducing agent and amino acid dispersant; the suspension stabilizer is a composite system of sodium alginate propylene glycol ester and aluminum silicate; the defoamer is a polyether-modified organosilicon defoamer; the seepage-proof and water-repellent agent is a composite system of sodium methylsilicate and calcium stearate; and the compacting reinforcing component is zirconium microsilica powder.

[0009] Furthermore, the weight ratio of the ultrafine ordinary silicate cement to the ultrafine sulfoaluminate cement is 4:1-6:1, and the specific surface area of ​​both is 1000-1200 m². 2 / kg.

[0010] Furthermore, the specific surface area of ​​the wear-resistant powder is 1200-1500 m². 2 / kg; the particle size of the zirconium microsilica powder is less than 1μm.

[0011] Furthermore, the particle size of the waste ceramic wear-resistant fine aggregate is 0.375-4.75 mm, and the particle size of the waste ceramic wear-resistant coarse aggregate is 5-10 mm.

[0012] Furthermore, both the waste ceramic wear-resistant fine aggregate and the waste ceramic wear-resistant coarse aggregate are prepared through modification treatment. The preparation process is as follows: crushing, screening, water washing, silica sol soaking for surface modification, and drying. The silica sol is an alkaline silica sol with a particle size of 20-50 nm.

[0013] Furthermore, according to claim 2, the ultra-early strength abrasion-resistant concrete is characterized in that the weight ratio of the polycarboxylate high-performance water-reducing agent to the amino acid dispersant is 1:1-3:1, and the weight ratio of the sodium alginate propylene glycol ester to aluminum silicate is 3:1-7:1.

[0014] Furthermore, the weight ratio of sodium methylsilicate to calcium stearate in the waterproofing and water-repellent agent is 1:1 to 4:1.

[0015] On the other hand, the present invention also provides a method for preparing the above-mentioned ultra-early strength abrasion-resistant concrete, characterized by comprising the following steps: S1, mixing and stirring ultrafine cement, abrasion-resistant powder, water-reducing dispersant, suspension stabilizer, defoamer, impermeable and water-repellent agent, and compacting reinforcing component evenly to obtain a premix; S2, adding waste ceramic abrasion-resistant fine aggregate and waste ceramic abrasion-resistant coarse aggregate to the premix, stirring evenly to obtain ultra-early strength abrasion-resistant concrete dry material.

[0016] Furthermore, the prepared dry concrete material is mixed with mixing water to form a concrete mixture, with the mass ratio of mixing water to premix being 0.28-0.32.

[0017] Beneficial effects of this invention: (1) This invention uses an ultrafine cement compound system combined with a composite water-reducing dispersant, a suspension stabilizer and a defoamer to effectively optimize the state of the concrete paste. The prepared concrete mixture has excellent workability, with a slump spread of over 600 mm, and possesses self-leveling and self-compacting properties; at the same time, the paste has excellent stability, with no bleeding, segregation or stratification problems during construction, moderate viscosity, and fine and smooth molding. It does not require complex vibration processes, greatly simplifies construction operations, improves construction efficiency, and is suitable for various on-site pouring construction scenarios.

[0018] (2) This invention innovatively adopts a composite system of ultrafine ordinary Portland cement and ultrafine sulfoaluminate cement. Relying on the high cementitious efficiency of ultrafine cement with high specific surface area, and combined with the early strength characteristics and micro-expansion effect of sulfoaluminate cement, it achieves rapid improvement and stable development of mechanical properties. The compressive strength of concrete can reach more than 20MPa after 2 hours, with significant ultra-early strength characteristics. It can meet the stringent requirements of rapid construction scenarios such as flood control and disaster reduction, road repair, and airport runway repair, and significantly shorten the construction and maintenance cycle. At the same time, there is no shrinkage problem in the later stage of strength. The mechanical properties continue to grow steadily at 28 days and 56 days, ensuring the long-term mechanical stability of the structure and solving the technical pain point of low early strength and inability to be put into use quickly in traditional concrete.

[0019] (3) This invention constructs a multi-layered wear-resistant and dense protective system, fundamentally improving the durability of concrete. On the one hand, it uses coarse and fine aggregates of waste ceramics modified with silica sol, combined with wear-resistant components such as high-hardness corundum powder and glass powder, to form a dual wear-resistant mechanism, which greatly improves the surface hardness of concrete and its impact and erosion resistance, effectively resisting damage such as high-speed sand-containing water flow, mud and sand impact, and heavy-load friction; on the other hand, through the micro-aggregate filling effect of zirconium microsilica powder and the hydrophobic and seepage-proofing effect of water-repellent agent, the internal porosity of concrete is reduced in a synergistic way, and the internal pore structure is optimized. The concrete impermeability grade can reach >P12, the electrical flux is extremely low, and the impermeability, water resistance and cavitation resistance are excellent. It can effectively cope with the complex and harsh service environment of water conservancy, transportation, ports, etc., significantly extend the service life of engineering structures, and reduce the later operation and maintenance costs.

[0020] (4) This invention abandons the traditional model of concrete that consumes large amounts of natural sand and gravel resources. It uses waste household ceramics and waste ceramic bricks as core coarse and fine aggregate raw materials, and realizes the resource reuse of solid waste through a simple modification process. This effectively solves the environmental problems of pollution and disposal difficulties caused by the accumulation of ceramic solid waste, while significantly reducing the mining of natural mineral resources and alleviating the industry's predicament of a shortage of high-quality building materials. This raw material system is low-cost, green and environmentally friendly, and the preparation process is simple and controllable. It does not require expensive fibers and other additives. While ensuring high performance, it effectively reduces the material production cost. It is a green and environmentally friendly building material with good market promotion value and social benefits. Detailed Implementation

[0021] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, specific embodiments of the present invention will be described in detail below.

[0022] It should be noted that, in the description of the embodiments of this application, the term "some specific embodiments" means that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same implementation or instance. Moreover, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0023] In this embodiment, "within the range" includes the values ​​at both ends, such as "within the range of 1 to 100", which includes the values ​​at both ends of 1 and 100.

[0024] This invention provides an ultra-early strength abrasion-resistant concrete, comprising the following components in parts by weight: 535-610 parts ultrafine cement, 20-55 parts abrasion-resistant powder, 510-625 parts waste ceramic abrasion-resistant fine aggregate, 755-910 parts waste ceramic abrasion-resistant coarse aggregate, 0.8-1.6 parts water-reducing dispersant, 1.2-1.9 parts suspension stabilizer, 0.12-0.18 parts defoamer, 2-8 parts impermeable and water-repellent agent, and 4-12 parts compacting reinforcement component.

[0025] Specifically, ultrafine cement includes ultrafine ordinary Portland cement and ultrafine sulfoaluminate cement. Using ultrafine cement improves the cement's cementitious efficiency and imparts higher early strength. In addition, sulfoaluminate cement further improves early strength, and the micro-volume expansion generated by its hydration can compensate for some of the shrinkage of the slurry system. Ordinary Portland cement can provide higher later strength and ensure the stable and continuous development of mechanical properties.

[0026] Wear-resistant powder includes at least one of corundum powder and glass powder. By adding corundum powder and glass powder with high hardness and wear resistance and erosion resistance, the surface hardness and erosion resistance of concrete are improved.

[0027] The wear-resistant fine aggregate and coarse aggregate from waste ceramics include one type of waste household ceramics and waste ceramic bricks. Through water washing, silica sol soaking for surface modification, and drying processes, the surface condition is improved, the interfacial transition zone is strengthened, and it has good bonding with cement hydration products, making waste ceramics a viable alternative to natural sand and gravel aggregates in concrete. Combined with the dual wear-resistant mechanism of wear-resistant powder and waste ceramic aggregates, it solves the problem of insufficient abrasion resistance in traditional wear-resistant concrete.

[0028] The water-reducing and dispersing agents include polycarboxylate high-performance water-reducing agents and amino acid dispersants; the suspension stabilizers include sodium alginate propylene glycol ester and aluminum silicate; and the defoamer is a polyether-modified organosilicon defoamer. This invention uses water-reducing and dispersing agents to ensure a highly fluid and uniformly dispersed concrete mixture that self-levels and self-compacts during construction. Combined with the action of the suspension stabilizer, the slurry remains stable, maintaining a uniform and consistent consistency throughout construction, preventing water loss, bleeding, stratification, and segregation. Simultaneously, the introduction of defoamers eliminates micro-bubbles within the concrete mixture, resulting in a smooth and fine concrete.

[0029] The water-repellent and impermeable agent includes sodium methylsilicate and calcium stearate, and the compacting reinforcing component is zirconium silicate powder. This invention employs an internal admixture method to add the water-repellent and impermeable agent, giving the hardened body a hydrophobic and impermeable effect. Combined with the compacted reinforcing component and the particle size distribution of ultrafine cement and wear-resistant powder, the system's porosity is reduced, increasing the concrete's density, further improving its impermeability and abrasion resistance, and enhancing its durability.

[0030] Preferably, the specific surface area of ​​ultrafine ordinary silicate cement and ultrafine sulfoaluminate cement is 1000 m². 2 / kg to 1200m 2 Within the range of / kg.

[0031] Preferably, the specific surface area of ​​the wear-resistant powder is 1200 m². 2 / kg to 1500m 2 Within the range of / kg.

[0032] Preferably, the particle size of the waste ceramic wear-resistant fine aggregate is in the range of 4.75 mm to 0.375 mm.

[0033] Preferably, the particle size of the waste ceramic wear-resistant coarse aggregate is in the range of 10mm to 5mm.

[0034] Furthermore, the waste ceramic wear-resistant fine aggregate and waste ceramic wear-resistant coarse aggregate are prepared by sequentially undergoing crushing, screening, water washing, silica sol soaking for surface modification, and drying processes.

[0035] Furthermore, the silica sol is an alkaline silica sol with a particle size of 20-50 nm.

[0036] Preferably, the weight ratio of polycarboxylate superplasticizer to amino acid dispersant is in the range of 1:1 to 3:1.

[0037] Preferably, the weight ratio of sodium alginate to aluminum silicate is in the range of 3:1 to 7:1.

[0038] Preferably, the weight ratio of sodium methylsilicate to calcium stearate is in the range of 1:1 to 4:1.

[0039] Preferably, the particle size of the zirconium microsilica powder is less than 1 μm.

[0040] Therefore, the ultra-early strength abrasion-resistant concrete provided by this invention has good workability, stable slurry, appropriate viscosity, and can achieve self-leveling and self-compacting; it has high early and late strength, low porosity, high density, good impermeability, and good water and abrasion resistance, ensuring service life even under complex conditions. Most of the main raw materials are waste ceramic solid waste, which utilizes solid waste resources, saves resources, reduces costs, and is an environmentally friendly material, promoting the secondary utilization of solid waste resources.

[0041] Another embodiment of the present invention provides a method for preparing the above-described ultra-early strength impact-resistant concrete, comprising the following steps: S1. Mix ultrafine cement, abrasion-resistant powder, water-reducing dispersant, suspension stabilizer, defoamer, impermeable and water-repellent agent and compacting reinforcing component evenly to obtain a premix; S2. Add waste ceramic wear-resistant fine aggregate and waste ceramic wear-resistant coarse aggregate to the premix, and stir evenly to obtain ultra-early strength impact-resistant dry concrete.

[0042] Furthermore, the method also includes the step of mixing the ultra-early strength abrasion-resistant concrete dry material with mixing water to form a concrete mixture for construction; wherein the ratio of the mixing water to the premix is ​​in the range of 0.28 to 0.32.

[0043] Based on the above embodiments, the present invention provides specific examples of the preparation method of ultra-early strength impact-resistant concrete to further illustrate the present invention. The polycarboxylate high-performance water-reducing agent is PC-733 type polycarboxylate high-performance water-reducing agent produced by Wuhan Tapai Huaxuan New Material Technology Co., Ltd., the amino acid dispersant is AJ-806 type amino acid dispersant produced by Wuhan Tapai Huaxuan New Material Technology Co., Ltd., and the defoamer is P803 type polyether modified organosilicon defoamer from BASF (China) Co., Ltd.

[0044] It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Experimental methods in the following embodiments, unless otherwise specified, are generally performed according to the manufacturer's recommended conditions. Unless otherwise stated, percentages and parts are by weight.

[0045] Example 1 This embodiment provides a method for preparing ultra-early strength impact-resistant concrete, including the following steps: 1) Weigh each raw material according to the proportions. The raw materials and their quantities include: 560 kg of ultrafine cement (467 kg of ultrafine ordinary silicate cement, 93 kg of ultrafine sulfoaluminate cement), 20 kg of wear-resistant powder (18 kg of corundum powder, 2 kg of glass powder), 510 kg of waste ceramic wear-resistant fine aggregate, 910 kg of waste ceramic wear-resistant coarse aggregate, 0.8 kg of water-reducing and dispersing agent (0.4 kg of polycarboxylate high-performance water-reducing agent, 0.4 kg of amino acid dispersant), 1.2 kg of suspension stabilizer (1.05 kg of sodium alginate propylene glycol ester, 0.15 kg of aluminum silicate), 0.12 kg of defoamer, 2 kg of impermeable and water-repellent agent (1 kg of sodium methylsilicate, 1 kg of calcium stearate), and 4 kg of dense reinforcing component; 2) Weigh out the ultrafine cement, wear-resistant powder, water-reducing dispersant, suspension stabilizer, defoamer, impermeable and water-repellent agent, and compacting reinforcement components and add them to the mixer in sequence. Mechanically stir to form a uniform mixture. Then, add the waste ceramic wear-resistant fine aggregate and waste ceramic wear-resistant coarse aggregate to the mixer and continue to stir and mix evenly to obtain the ultra-early strength impact-resistant concrete dry material. Weigh out 174.4 kg of mixing water and mix it with the ultra-early strength impact-resistant concrete dry material to form a uniform slurry, which can then be used for construction.

[0046] Example 2 This embodiment provides a method for preparing ultra-early strength impact-resistant concrete, which differs from Embodiment 1 in that: In step 1), the raw materials and their quantities include: 560 kg of ultrafine cement (467 kg of ultrafine ordinary silicate cement and 93 kg of ultrafine sulfoaluminate cement), 25 kg of wear-resistant powder (20 kg of corundum powder and 5 kg of glass powder), 536 kg of waste ceramic wear-resistant fine aggregate, 887 kg of waste ceramic wear-resistant coarse aggregate, 1 kg of water-reducing and dispersing agent (0.6 kg of polycarboxylate high-performance water-reducing agent and 0.4 kg of amino acid dispersant), 1.4 kg of suspension stabilizer (1.2 kg of sodium alginate and 0.2 kg of aluminum silicate), 0.14 kg of defoamer, 3 kg of impermeable and water-repellent agent (2 kg of sodium methylsilicate and 1 kg of calcium stearate), and 6 kg of compacting and reinforcing component; In step 2), 181.5 kg of water was used for mixing; the other steps were the same as in Example 1.

[0047] Example 3 This embodiment provides a method for preparing ultra-early strength impact-resistant concrete, which differs from Embodiment 1 in that: In step 1), the raw materials and their quantities include: 578 kg of ultrafine cement (482 kg of ultrafine ordinary silicate cement, 96 kg of ultrafine sulfoaluminate cement), 36 kg of wear-resistant powder (29 kg of corundum powder, 7 kg of glass powder), 564 kg of waste ceramic wear-resistant fine aggregate, 842 kg of waste ceramic wear-resistant coarse aggregate, 1.2 kg of water-reducing and dispersing agent (0.7 kg of polycarboxylate high-performance water-reducing agent, 0.5 kg of amino acid dispersant), 1.5 kg of suspension stabilizer (1.2 kg of sodium alginate propylene glycol ester, 0.3 kg of aluminum silicate), 0.15 kg of defoamer, 5 kg of impermeable and water-repellent agent (2.8 kg of sodium methylsilicate, 2.2 kg of calcium stearate), and 8.5 kg of dense reinforcing component; In step 2), 184.2 kg of water was used for mixing; the other steps were the same as in Example 1.

[0048] Example 4 This embodiment provides a method for preparing ultra-early strength impact-resistant concrete, which differs from Embodiment 1 in that: In step 1), the raw materials and their quantities include: 592 kg of ultrafine cement (475 kg of ultrafine ordinary silicate cement, 117 kg of ultrafine sulfoaluminate cement), 42 kg of wear-resistant powder (34 kg of corundum powder, 8 kg of glass powder), 593 kg of waste ceramic wear-resistant fine aggregate, 797 kg of waste ceramic wear-resistant coarse aggregate, 1.5 kg of water-reducing and dispersing agent (1 kg of polycarboxylate high-performance water-reducing agent, 0.5 kg of amino acid dispersant), 1.7 kg of suspension stabilizer (1.3 kg of sodium alginate propylene glycol ester, 0.4 kg of aluminum silicate), 0.17 kg of defoamer, 6.5 kg of impermeable and water-repellent agent (5 kg of sodium methylsilicate, 1.5 kg of calcium stearate), and 10.2 kg of compacting and reinforcing component; In step 2), 183.8 kg of water was used for mixing; the other steps were the same as in Example 1.

[0049] Example 5 This embodiment provides a method for preparing ultra-early strength impact-resistant concrete, which differs from Embodiment 1 in that: In step 1), the raw materials and their quantities include: 608 kg of ultrafine cement (507 kg of ultrafine ordinary silicate cement, 101 kg of ultrafine sulfoaluminate cement), 54 kg of wear-resistant powder (44 kg of corundum powder, 10 kg of glass powder), 625 kg of waste ceramic wear-resistant fine aggregate, 750 kg of waste ceramic wear-resistant coarse aggregate, 1.6 kg of water-reducing and dispersing agent (0.9 kg of polycarboxylate high-performance water-reducing agent, 0.7 kg of amino acid dispersant), 1.9 kg of suspension stabilizer (1.5 kg of sodium alginate propylene glycol ester, 0.4 kg of aluminum silicate), 0.18 kg of defoamer, 8 kg of impermeable and water-repellent agent (6.2 kg of sodium methylsilicate, 1.8 kg of calcium stearate), and 12 kg of dense reinforcing component; In step 2), 192 kg of water is used for mixing; the other steps are the same as in Example 1.

[0050] Comparative Example 1 Weigh out 592 kg of P•O 42.5 grade cement, 42 kg of silica fume, 593 kg of manufactured sand fine aggregate, 797 kg of crushed stone coarse aggregate, and 1 kg of polycarboxylate high-performance water-reducing agent. Mix the above raw materials evenly, take 183.8 kg of mixing water, mix it with the dry concrete material, stir evenly, and then test and use it.

[0051] Comparative Example 2 Weigh out 592 kg of P•O 42.5 grade cement, 42 kg of silica fume, 593 kg of waste ceramic wear-resistant fine aggregate, 797 kg of waste ceramic wear-resistant coarse aggregate, and 1 kg of polycarboxylate high-performance water-reducing agent. Mix the above raw materials evenly, take 183.8 kg of mixing water, mix it with the dry concrete material, stir evenly, and then test and use it.

[0052] Comparative Example 3 Weigh out 592 kg of ultrafine cement (475 kg of ultrafine ordinary Portland cement and 117 kg of ultrafine sulfoaluminate cement), 42 kg of silica fume, 593 kg of waste ceramic wear-resistant fine aggregate, 797 kg of waste ceramic wear-resistant coarse aggregate, 1.5 kg of water-reducing dispersant (1 kg of polycarboxylate high-performance water-reducing agent and 0.5 kg of amino acid dispersant), and 0.17 kg of defoamer. Mix the above raw materials evenly, take 183.8 kg of mixing water, mix it with the dry concrete material, stir evenly, and then test and use it.

[0053] Comparative Example 4 Weigh out 592 kg of ultrafine cement (475 kg of ultrafine ordinary Portland cement and 117 kg of ultrafine sulfoaluminate cement), 42 kg of silica fume, 593 kg of waste ceramic wear-resistant fine aggregate, 797 kg of waste ceramic wear-resistant coarse aggregate, 1.5 kg of water-reducing and dispersing agent (1 kg of polycarboxylate high-performance water-reducing agent and 0.5 kg of amino acid dispersant), 1.9 kg of suspension stabilizer (1.5 kg of sodium alginate and 0.4 kg of aluminum silicate), 0.17 kg of defoamer, and 8 kg of impermeable and water-repellent agent (6.2 kg of sodium methylsilicate and 1.8 kg of calcium stearate). Mix the above raw materials evenly, take 183.8 kg of mixing water, mix it with the dry concrete material, stir evenly, and then test and use it.

[0054] The ultra-early strength abrasion-resistant concretes obtained in Examples 1-5 and Comparative Examples 1-4 were tested for workability, paste stability, strength, abrasion resistance and impermeability, and the results are shown in Table 1.

[0055] Table 1. Test results of ultra-early strength impact-resistant concrete obtained in Examples 1-5 and Comparative Examples 1-4

[0056] As can be seen from Table 1, Examples 1-5 of this invention use ultrafine cement, wear-resistant powder, and wear-resistant coarse and fine aggregates as the main raw material system, combined with functional components such as water-reducing dispersant, suspension stabilizer, impermeable and water-repellent agent, and compacting reinforcing component. This results in workability, mechanical properties, abrasion resistance, and impermeability significantly higher than Comparative Examples 1-4. Comparative Example 1 uses existing ordinary concrete mix proportions, resulting in poor performance in all aspects. Comparative Example 2 uses a wear-resistant aggregate mix proportion without adding functional components, resulting in generally average performance, but significantly enhanced abrasion resistance. Comparative Example 3, based on Comparative Example 2, uses ultrafine cement and water-reducing dispersant, and adds defoamer, improving fluidity, bleeding, and stratification to some extent. Comparative Example 4, based on Comparative Example 3, adds suspension stabilizer and impermeable and water-repellent agent, further improving workability and impermeability, and thus improving mechanical properties to some extent. However, it lacks the combined effect of wear-resistant powder, compacting reinforcing component, and other components found in this invention, and its overall performance is lower than that of the examples of this invention.

[0057] In summary, the workability, slurry stability, strength, abrasion resistance, and impermeability of the ultra-early strength abrasion-resistant concrete based on solid waste obtained in this embodiment are all superior to those of ordinary concrete.

[0058] While the present invention has been disclosed above, its scope of protection is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention, and all such changes and modifications will fall within the scope of protection of the present invention.

Claims

1. An ultra-early-strength, impact-resistant concrete, characterized in that, It is composed of the following components in parts by weight: 535-610 parts ultrafine cement, 20-55 parts wear-resistant powder, 510-625 parts waste ceramic wear-resistant fine aggregate, 755-910 parts waste ceramic wear-resistant coarse aggregate, 0.8-1.6 parts water-reducing dispersant, 1.2-1.9 parts suspension stabilizer, 0.12-0.18 parts defoamer, 2-8 parts impermeable and water-repellent agent, and 4-12 parts compacting and reinforcing components.

2. The ultra-early strength abrasion-resistant concrete according to claim 1, characterized in that, The ultrafine cement is a composite system of ultrafine ordinary silicate cement and ultrafine sulfoaluminate cement; the wear-resistant powder is at least one of corundum powder and glass powder; the waste ceramic wear-resistant fine aggregate and waste ceramic wear-resistant coarse aggregate are both selected from waste household ceramics and waste ceramic bricks; the water-reducing and dispersing agent is a composite system of polycarboxylate high-performance water-reducing agent and amino acid dispersant; the suspension stabilizer is a composite system of sodium alginate propylene glycol ester and aluminum silicate; the defoamer is a polyether-modified organosilicon defoamer; the seepage-proof and water-repellent agent is a composite system of sodium methylsilicate and calcium stearate; and the compacting and reinforcing component is zirconium microsilica powder.

3. The ultra-early strength impact-resistant concrete according to claim 2, characterized in that, The weight ratio of the ultrafine ordinary silicate cement to the ultrafine sulfoaluminate cement is 4:1-6:1, and the specific surface area of ​​both is 1000-1200 m². 2 / kg.

4. The ultra-early strength impact-resistant concrete according to claim 2, characterized in that, The specific surface area of ​​the wear-resistant powder is 1200-1500 m². 2 / kg; the particle size of the zirconium microsilica powder is less than 1μm.

5. The ultra-early strength impact-resistant concrete according to claim 2, characterized in that, The particle size of the waste ceramic wear-resistant fine aggregate is 0.375-4.75 mm, and the particle size of the waste ceramic wear-resistant coarse aggregate is 5-10 mm.

6. The ultra-early strength impact-resistant concrete according to claim 5, characterized in that, Both the waste ceramic wear-resistant fine aggregate and the waste ceramic wear-resistant coarse aggregate are prepared through modification treatment. The preparation process is as follows: crushing, screening, water washing, surface modification by silica sol immersion, and drying. The silica sol is an alkaline silica sol with a particle size of 20-50nm.

7. The ultra-early strength impact-resistant concrete according to claim 2, characterized in that, The weight ratio of the polycarboxylic acid high-performance water-reducing agent to the amino acid dispersant is 1:1-3:1, and the weight ratio of sodium alginate propylene glycol ester to aluminum silicate is 3:1-7:

1.

8. The ultra-early strength impact-resistant concrete according to claim 2, characterized in that, The weight ratio of sodium methylsilicate to calcium stearate in the impermeable and water-repellent agent is 1:1 to 4:

1.

9. A method for preparing ultra-early strength impact-resistant concrete according to any one of claims 1-8, characterized in that, Includes the following steps: S1. Mix ultrafine cement, wear-resistant powder, water-reducing dispersant, suspension stabilizer, defoamer, impermeable and water-repellent agent, and compacting reinforcement components evenly to obtain a premix; S2. Add waste ceramic wear-resistant fine aggregate and waste ceramic wear-resistant coarse aggregate to the premix, mix evenly, and obtain ultra-early strength impact-resistant and wear-resistant concrete dry material.

10. The method for preparing ultra-early strength impact-resistant concrete according to claim 9, characterized in that, The prepared dry concrete material is mixed with mixing water to form a concrete mixture, with the mass ratio of mixing water to premix being 0.28-0.32.